Prevalence of Salmonella spp. in layer and broiler farms in Palestine in 2018, with special emphasis on Salmonella enterica serovar Enteritidis - ABUSEIR, S; ABED AL-DAYM, M; ADWAN, G; KHRAIM, N (Journal of the Hellenic Veterinary Medical Society, 2021)
Salmonella spp. are one of a major public health concerns worldwide, as well as it is the most frequently isolated foodborne pathogen. Human illness with Salmonella spp. is often due to the consumption of contaminated food of animal origin such as eggs or their products and poultry meat. The prevalence of this pathogen in egg-laying poultry farms and in broiler farms is an important public health risk factor. Salmonella enterica serovar Enteritidis has been the major cause of foodborne salmonellosis in humans. Data on the prevalence of Salmonella spp. in the Palestinian territories’ poultry flocks is lacking. The objective of this study was to investigate the prevalence of Salmonella spp. in local layer and broiler flocks, and to find out the rate of S. Enteritidis among the isolated samples. A total of 1180 cloacal swabs were collected from several layer and broiler farms from different locations in the West Bank, Palestine. Identification of Salmonella spp. was carried out using conventional and serological methods. Molecular methods using Polymerase Chain Reaction was used for confirmation of Salmonella spp., and to detect the presence of S. Enteritidis among the isolated Salmonella spp. Results of the current study showed that, the rate of Salmonella spp. in the sample tested from layer and broiler farms was 10.7% (65/608) and 4.7% (27/572), respectively. In addition, the prevalence rate of S. Enteritidis among other Salmonella spp. was 0.0% and 14.8% for layer and broiler farms, respectively. It is highly recommended that further studies should be conducted, including high number of samples with serotyping and molecular characterization of the positive samples.